The Rise and Decline of Communist Czechoslovakia´s Railway Sector - Nigrin, Tomáš (Book collections on Project MUSE., 2022)
"Once the pride of interwar Czechoslovakia, and key during the forced industrialization of the Stalinist period, during the 1970s and 1980s the Czechoslovak railway sector showed the symptoms of the political tiredness and economic exhaustion of the Soviet Bloc. This book examines the failure of central economic planning through the lens of this national transport system.Based on the presentation of its history and on the detailed scrutiny of the actors, institutions, internal mechanisms, and conditions of the railway sector, the analysis reveals the identities of the real stakeholders in the state administration. This case shows how the country was governed by Communist Party institutions and government ministries, and how developments in the transportation sector-like in every sector-reflected their priorities. Numerous tables with selected statistics underscore the economic analysis and black and white photos offer a glimpse on the technical base of the railway sector.The book is filled with enlightening comparisons of the Czechoslovak transportation industry with its counterparts in the whole Eastern Bloc. Integration into the Council for Mutual Economic Assistance (Comecon) of the Bloc could have been an asset, yet the records have more to say about conflicts than cooperation"--